Implementation of a project based learning approach for the senior year and fourth course of secondary from Henri Becquerel Experimental High School - Fierro Echeverría, Samuel Enrique (2007)
1. Theoretical Framework. 2. Methodology. 3. Results and analysis of the research. 4. Conclusions and recommendations